Safety and immunogenicity of a mosquito saliva peptide-based vaccine: a randomised, placebo-controlled, double-blind, phase 1 trial. Issue 10242 (27th June 2020) - Manning, Jessica E; Oliveira, Fabiano; Coutinho-Abreu, Iliano V; Herbert, Samantha; Meneses, Claudio; Kamhawi, Shaden; Baus, Holly Ann; Han, Alison; Czajkowski, Lindsay; Rosas, Luz Angela; Cervantes-Medina, Adriana; Athota, Rani; et al.
Summary: Background: In animal models, immunity to mosquito salivary proteins protects animals against mosquito-borne disease. These findings provide a rationale to vaccinate against mosquito saliva instead of the pathogen itself. To our knowledge, no vector salivary protein-based vaccine has been tested for safety and immunogenicity in humans. We aimed to assess the safety and immunogenicity of Anopheles gambiae saliva vaccine (AGS-v), a peptide-based vaccine derived from four A gambiae salivary proteins, in humans. Methods: In this randomised, placebo-controlled, double-blind, phase 1 trial, participants were enrolled at the National Institutes of Health Clinical Center in Bethesda, MD, USA. Participants were eligible if they were healthy adults, aged 18–50 years with no history of severe allergic reactions to mosquito bites. Participants were randomly assigned (1:1:1), using block randomisation and a computer-generated randomisation sequence, to treatment with either 200 nmol of AGS-v vaccine alone, 200 nmol of AGS-v with adjuvant (Montanide ISA 51), or sterile water as placebo. Participants and clinicians were masked to treatment assignment. Participants were given a subcutaneous injection of their allocated treatment at day 0 and day 21, followed by exposure to feeding by an uninfected Aedes aegypti mosquito at day 42 to assess subsequent risk to mosquito bites in a controlled setting. The primary endpoints were safety and immunogenicity at day 42 after the first immunisation. Participants who were given at least one dose of assigned treatment were assessed for the primary endpoints and analysis was by intention to treat. The trial was registered with ClinicalTrials.gov, NCT03055000, and is closed for accrual. Findings: Between Feb 15 and Sept 10, 2017, we enrolled and randomly assigned 49 healthy adult participants to the adjuvanted vaccine (n=17), vaccine alone (n=16), or placebo group (n=16). Five participants did not complete the two-injection regimen with mosquito feeding at day 42, but were included in the safety analyses. No systemic safety concerns were identified; however, one participant in the adjuvanted vaccine group developed a grade 3 erythematous rash at the injection site. Pain, swelling, erythema, and itching were the most commonly reported local symptoms and were significantly increased in the adjuvanted vaccine group compared with both other treatment groups (nine [53%] of 17 participants in the adjuvanted vaccine group, two [13%] of 16 in the vaccine only group, and one [6%] of 16 in the placebo group; p=0·004). By day 42, participants who were given the adjuvanted vaccine had a significant increase in vaccine-specific total IgG antibodies compared with at baseline than did participants who were give vaccine only (absolute difference of log10 -fold change of 0·64 [95% CI 0·39 to 0·89]; p=0·0002) and who were given placebo (0·62 [0·34 to 0·91]; p=0·0001). We saw a significant increase in IFN-γ production by peripheral blood mononuclear cells at day 42 in the adjuvanted vaccine group compared with in the placebo group (absolute difference of log10 ratio of vaccine peptide-stimulated vs negative control 0·17 [95% CI 0·061 to 0·27]; p=0·009) but we saw no difference between the IFN-γ production in the vaccine only group compared with the placebo group (0·022 [–0·072 to 0·116]; p=0·63). Interpretation: AGS-v was well tolerated, and, when adjuvanted, immunogenic. These findings suggest that vector-targeted vaccine administration in humans is safe and could be a viable option for the increasing burden of vector-borne disease. Funding: Office of the Director and the Division of Intramural Research at the National Institute of Allergy and Infectious Diseases, and National Institutes of Health.